A quantitative study of China’s rehabilitation policies from the perspective of policy tools - Jiang, Xinyang; Luo, Li (Frontiers in Public Health, 2025)
PurposeRehabilitation policies constitute a critical guiding framework for national and regional development. This study aims to use policy tools to analyze the specific content and structural characteristics of China’s rehabilitation-related policies from 2010 to 2023, and provide a new reference perspective for international rehabilitation policy research.Materials and methodsA three-dimensional analytical framework of “policy tool type–policy theme characteristic–stakeholder” was developed. Data were drawn from nation-level policies on rehabilitation medical services issued by the State Council of the People’s Republic of China and the National Health Commission. Based on established inclusion and exclusion criteria, 41 valid policy documents were selected. NVivo (release 14.23.1) was used for four-level coding, and reliability and validity tests were conducted. Policy texts were first quantified, followed by descriptive analysis.ResultsA total of 298 codes were identified. Among policy tool types, environmental tools accounted for the highest proportion (58.05%), followed by supply-side tools (32.98%), while demand-side tools had the lowest proportion (9.06%). From the stakeholder perspective, provider organizations (42.95%) were the core target, followed by regulatory authorities (19.13%) and rehabilitation service recipients (19.80%). Clinical practitioners and the rehabilitation capital market each accounted for 9.06%, with most of the policies related to passive response-type policies.ConclusionChina’s current rehabilitation medical service policies have insufficient use of supply-side and demand-side tools, and uneven policy coverage among stakeholders. The structural application of policy tools should be optimized, particularly by strengthening the role of demand-side policy tools.